The Grammar of Spoken Language or the Grammar of Standard Language? - Fatima-Zohra SEMAKDJI (Revue des Sciences Humaines)
In the light of the fast-developing technology which is encouraging spontaneous global communication, conversational skills have become an inestimable asset. Natural conversation calls for the use of certain interactive and interpersonal structures which only spoken grammar (the grammar of conversation) can offer. However, almost all accounts of English grammar have been based, to a very high extent, on the standard version of the language. Through this paper, we set out to demonstrate the significant contribution of spoken grammar to natural conversation. Light is shed on the distinct nature of spoken grammar, as opposed to the nature of standard grammar, with a special focus on the interactive and interpersonal aspects of spoken grammar. The study aims at investigating the extent to which spoken grammar is used by students and the viability of teaching spoken grammar in order to make students’ conversational English more natural. It will also provide information about whether spoken grammar is taught, the way it is presented and the teachers’ views about the usefulness of integrating aspects of spoken grammar into the teaching of speaking.